Odpowiedź :
Rozwiązanie :
[tex]a] \ \frac{4}{\sqrt2}\cdot\frac{\sqrt2}{\sqrt2}=\frac{4\sqrt2}{\sqrt{2^2}}=\frac{4\sqrt2}{2}=2\sqrt2\approx2\cdot1,4\approx2,8\\\\b] \ \frac{6}{\sqrt3}\cdot\frac{\sqrt3}{\sqrt3}=\frac{6\sqrt3}{\sqrt{3^2}}=\frac{6\sqrt3}{3}=2\sqrt3\approx2\cdot1,7=3,4\\\\c] \ \frac{2}{3\sqrt2}\cdot\frac{\sqrt2}{\sqrt2}=\frac{2\sqrt2}{3\sqrt{2^2}}=\frac{2\sqrt2}{6}=\frac{\sqrt2}{3}\approx\frac{1,4}{3}\approx0,47\\\\d] \ \frac{3}{5\sqrt3}\cdot\frac{\sqrt3}{\sqrt3}=\frac{3\sqrt3}{5\sqrt{3^2}}=\frac{3\sqrt3}{15}=[/tex]
Dokończenie, bo za długa formuła :
[tex]=\frac{\sqrt3}{5}\approx\frac{1,7}{5}\approx0,34[/tex]
25.
Usuwamy niewymierność w mianowniku każdej z podanych liczb niewymiernych.
a) 4/√2=4/√2 ·√2/√2=(4·√2)/(√2·√2)=4√2/2=2√2
2√2 ≈ 2·1,4=2,8
b) 6/√3=6/√3 ·√3/√3=(6√3)/(√3·√3)=6√3/3=2√3
2√3 ≈2·1,7=3,4
c) 2/3√2=2/3√2 ·√2/√2=2√2/3·2=√2/3
√2/3 ≈1,4/3=0,4(6)
d) 3/5√3=3√3/5·3=√3/5
√3/5 ≈1,7/5=0,34